FAKTOR YANG MEMPENGARUHI KINERJA PARUH WAKTU WANITA PADA HOME INDUSTRY PASCA COVID-19 - Nurul Badriyah; Ulfah, Elisa Robiatul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
According to the BPS, female part-time workers became massive during the Covid-19 pandemic as a result of the pandemic. The home industry has a good role in absorbing female workers, especially during the Covid-19 pandemic. The objective of this research is to identify the effect of time spent for working, wages and level of education on the performance of female part-timers in the home industry post the Covid-19 in Kediri Regency. The data of this quantitative research was harvested from questionnaires distributed to 154 respondents. The data analysis used is multiple linear regression analysis. The results of this research show that the data is free from classical assumption problems, besides that the variables of working time, wages and level of education have a significant positive effect on female’s part-time performance. The implication of this research is that it is necessary to improve the wage system, and it is necessary to increase the ability of human resources so that performance is better.